Position and Development of School-Geography in Switzerland - Reinfried, Sibylle (Journal of Geography Education, 2004)
This paper describes the position of geography within the field of school disciplines from grade 1 to 12 (K12) and details the subject’s objectives in the syllabi. Syllabi as well as textbooks reflect the different scientific approaches and traditions in multicultural Switzerland. In German-speaking Switzerland, which puts the main emphasis on content relating to physical geography, school-geography is organized along the structure of scientific geography. Learning is the result of application of the cognitivist paradigm by clarifying geographical facts, establishing the context and solving problems. In French-speaking Switzerland (Cantons Geneva and Vaud), school-geography is being regarded as social geography. Here, beginning in the mid-90s, syllabi and textbooks comply with constructivist concepts. Subject matter and insights are being constructed with the help of integrative concepts and key questions. Among the challenges geography education will increasingly have to face, there is the integration of the key problems of humanity in the 21st century (refugees, migration, minorities, human rights, securing peace) into classroom-teaching, the increasing importance of the computer in the classroom, bilingual instruction (French-German and English-German) as well as the standardization of teaching content and aims. Unsolved problems of Swiss geography education are the neglect of the area over decades in Switzerland and the inadequate cooperation between the science of geography and geography education.